Effects of morphine and other drugs with antagonist and mixed agonist-antagonist properties upon behavious maintained by a schedule of interresponse time reinforcement - Adam-Carriere, Dyane (University of Ottawa (Canada), 1977)
Abstract not available.
Keywords: Health Sciences, Pharmacology.; Biology, Physiology.